Safety Strategies of Genetically Engineered T Cells in Cancer Immunotherapy - Ren, Yan-Bei (Curr Pharm Des, 2018)
T-cell therapy using genetically engineered T cells modified with either T cell receptor or chi-meric antigen receptor holds great promise for cancer immunotherapy. The concerns about its toxicities still remain despite recent successes in clinical trials. Temporal and spatial control of the engineered therapeutic T cells may improve the safety profile of these treatment regimens. To achieve these goals, numerous approaches have been tested and utilized including the incorporation of a suicide gene, the switch-mediated activation, the combinatorial antigen recognition, etc. This review will summarize the toxicities caused by engineered T cells and novel strategies to overcome them.